Mechanochemically Driven Radical Nitration of Electron-Rich ortho and para Di- and Trialkoxyarenes Using Iron(III) Nitrate - Andrejčák, Samuel; Dudáš, Peter; Májek, Michal (Synlett, 2025)
This study introduces a sustainable mechanochemical approach for the nitration of electron-rich ortho and para di- and trialkoxyarenes using iron(III) nitrate nonahydrate (Fe(NO3)3·9H2O) as a source of nitro radicals. Conventional nitration methods require harsh conditions and hazardous reagents, limiting their application. Herein, mechanochemical activation offers a rapid and efficient alternative with minimal solvent and a reduced reaction time. Screening identified Fe(NO3)3 as the most effective nitrating agent, with successful application with a variety of ortho and para di- and trialkoxyarenes while maintaining high regioselectivity. The scalability and environmental benefits of the method underscore its potential in organic synthesis, advancing a practical, green protocol for radical aromatic nitration.
Keywords: radicals; mechanochemistry; nitration; arenes; nitryl radical; iron(III) nitrate; liquid-assisted grinding